Survey of Pesticide Use in Farms: Khno Kaen Province, Thailand(Thai) - Ussanawarong, Skulrat; Peingsaweung, Natasoratun; Chabangam, Sunti (Asia-Pacific Journal of Science and Technology, 2017)
The massive use oftoxic pesticides will have undersirable effects and will impact users and consumer health. The objectives of this research are to study which type of pesticides are the most frequently used by farmers in Khon Kaen province, to study the sources of pesticides and to study the distribution offarmers, vegetables. The research was conducted from June to September 2004 by interviews with 255 farmers from 255 families in Khon Kaen province. The research found that the majority of the farmers purchased their pesticides in Khon Kaen province (95.29%). The market in Muang District was the place where most vegetables were sold (68.630/ o ) and at other markets in Khon Kaen province (30.20%). The farmers used various kinds of pesticides for almost every type of vegetable. The pesticide which was very popular among farmers was Folidol (parathion methyl). [n addition there were 3 more pesticides which are banned: mevinphos, monocrotophos and methamidophos. We suggest that the farmers and pesticide store keepers should be informed, and be aware of the danger of forbidden pesticides. Farmers shou)d use and store keepers sell low toxicity pesticides, In policy it should be illegal to manufacture and distribute these toxic chemicals. Therefore, there should bc penalties for those who break the law and pesticide use should be monitored regularly for verifiable efficiency of control.